Development of β-cyclodextrin/polyvinypyrrolidone-co-poly (2-acrylamide-2-methylpropane sulphonic acid) hybrid nanogels as nano-drug delivery carriers to enhance the solubility of Rosuvastatin: An in vitro and in vivo evaluation - Shoukat, Hina; Pervaiz, Fahad; Khan, Mehran; Rehman, Sadia; Akram, Faizan; Abid, Usman; Noreen, Sobia; Nadeem, Muhammad; Qaiser, Rubina; Ahmad, Rizwan; Farooq, Irshad (PLOS ONE, 2022)
The present study is aimed at enhancing the solubility of rosuvastatin (RST) by designing betacyclodextrin/polyvinypyrrolidone-co-poly (2-acrylamide-2-methylpropane sulphonic acid) crosslinked hydrophilic nanogels in the presence of crosslinker methylene bisacrylamide through free-radical polymerization method. Various formulations were fabricated by blending different amounts of betacyclodextrin, polyvinylpyrrolidone, 2-acrylamide-2-methylpropane sulphonic acid, and methylene bisacrylamide. The developed chemically crosslinked nanogels were characterized by FTIR, SEM, PXRD, TGA, DSC, sol-gel analysis, zeta size, micromeritics properties, drug loading percentage, swelling, solubility, and release studies. The FTIR spectrum depicts the leading peaks of resultant functional groups of blended constituents while a fluffy and porous structure was observed through SEM images. Remarkable reduction in crystallinity of RST in developed nanogels revealed by PXRD. TGA and DSC demonstrate the good thermal stability of nanogels. The size analysis depicts the particle size of the developed nanogels in the range of 178.5 ±3.14 nm. Drug loading percentage, swelling, solubility, and release studies revealed high drug loading, solubilization, swelling, and drug release patterns at 6.8 pH paralleled to 1.2 pH. In vivo experiments on developed nanogels in comparison to marketed brands were examined and better results regarding pharmacokinetic parameters were observed. The compatibility and non-toxicity of fabricated nanogels to biological systems was supported by a toxicity study that was conducted on rabbits. Efficient fabrication, excellent physicochemical properties, improved dissolution, high solubilization, and nontoxic nanogels might be a capable approach for the oral administration of poorly water-soluble drugs.